METABOLIC DISORDERS IN CHILDREN WITH GASTROENTEROLOGICAL DISEASES AND FOOD ALLERGIES - Salomova F.I.; Qobiljonova Sh.R.; Kim E.S.; Kim E.S. (Bright Mind Publishing, 2025)
The prevalence of chronic non-infectious diseases of the gastrointestinal tract in children is constantly increasing and is, according to various authors, 300.0 to 663.1%, with the peak incidence occurring at the age of 6-7, 9-10 and 12 years with a maximum increase at 6 years. It has been proven that the formation of chronic pathology of the digestive organs begins in preschool age. Food allergy is present in the majority (70% and above) of children of younger age groups. It largely determines the background against which functional disorders and organic diseases of the digestive organs are formed. The presence of food sensitization in a child with a gastroenterological disease can be masked by the symptoms of the latter, which makes therapeutic and preventive measures in the patient less effective. The socio-economic conditions of life in our country that have changed significantly in the last 15-20 years, the deterioration of public health, including children's health, indicate the need for epidemiological studies of the prevalence and structure of gastroenterological diseases and food allergies in children, studying the features of changes in metabolic and immunological homeostasis, which will clarify their role and the allergic factor in the formation and development of this pathology, improve diagnostic and treatment methods. The solution to these issues is undoubtedly relevant and socially significant for pediatrics and medicine in general.